Modern and renewable materials in civil engineering - Brozovsky, Jiri (Trans Tech Publications Ltd, 2020)
Prepared to the 20th Anniversary of the Faculty of Civil Engineering of the VSB - Technical University of Ostrava Special topic volume with invited peer reviewed papers only.
Keywords: Sustainable development.; Renewable energy sources.; elektronické knihy; electronic books